If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3y-2=4y+9
We move all terms to the left:
3y-2-(4y+9)=0
We get rid of parentheses
3y-4y-9-2=0
We add all the numbers together, and all the variables
-1y-11=0
We move all terms containing y to the left, all other terms to the right
-y=11
y=11/-1
y=-11
| (6x+4)(4x+8)=84 | | 2(x+5)=5(x+3)-23 | | 3/5e-6=-2/5(1e-10)-7 | | 0=200-10x-5x^2 | | 22.8-v=v | | 19-6x=2x-65 | | 19-6a=2a-65 | | 250-x=180 | | 3x+7=2(x+4)+9 | | 4x+9-4x=76-3x | | (1+x)^2÷3+(1-x)^2÷3=4(1-x^2)^1÷3 | | a+81=6a+56 | | 3(x-5)+10=-5 | | 4x^2+5x−6=0 | | 4x2+5x−6=0 | | -7=2e-7 | | 90-x=26+3x | | (t+2)^3-64(t+2)=0 | | 20y+70=110 | | -4=-17+y | | 23-4x=-5 | | -3n^2-15n-12=0 | | 3(5+4y)=39 | | 19.2a=4a | | (3x+1.5)-(x+0.5)=3x-2 | | 12/x=6/5 | | 5^3x*25=5^3*125 | | 3.2a=20a | | 4b+b^2=84 | | W=2/t^2 | | 2+4y=y+14 | | 12x(3+74)=92 |